Kepemimpinan Spiritual Tuan Guru Haji Muhammad Mutawalli dalam Meningkatkan Sumber Daya Manusia Pendidik di Pondok Pesantren Darul Aitam Jerowaru - Hamdi, Miftahul; Yakin, Nurul; Sulhan, Ahmad (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
Tuan Guru Haji Muhammad Mutawalli's spiritual leadership has garnered attention due to his influence at the Darul Aitam Jerowaru Islamic Boarding School. The integrity of educational human resources in issue relates to the morals, ethics, honesty, accountability, and strong Islamic values that instructors and students embody. The goal of this study was to determine how Tuan Guru Haji Muhammad Mutawalli provided spiritual leadership at the Darul Aitam Jerowaru Islamic Boarding School and contributed to the integrity of Educational Human Resources. Qualitative research is a research approach based on the idea of postpositivism, with data collected using triangulation and inductive analytical procedures. The results of this study are spiritual leadership in the Islamic boarding school of the practice of the tarekat taught by Tuan Guru Haji Muhammad Mutawalli is through opening the Majlis Taklim, the Majlis pengajian for the general public, then the strategy used uses only the sharia approach and the role as the leader of the Islamic boarding school, Tuan Guru directs and organizes his students, so a Tuan Guru has a lot of charm and authority in front of his students.